Molecular alterations in glioblastoma multiforme: new directions and prospects - Jesionek-Kupnicka, Dorota; Pasz-Walczak, Grażyna; Kordek, Radzisław; Kubiak, Robert (Contemporary Oncology/Współczesna Onkologia, 2004)
Glioblastoma multiforme (GM, WHO GIV) is the most common primary tumor of the central nervous system with the most aggressive clinical course and fatal prognosis. Despite the intensive molecular and immunohistochemical investigations, and treatment efforts, a median survival still remains below one year. Both in vivo and in in vitro studies GM features significant resistance to the treatment in comparison to other neoplasms. The prognostic factors in glioblastoma are still controversial and not yet well established including PTEN mutations, EGFR amplification, especially with EGFRvIII overexpression, alterations in polymorphism of the EGF gene, the increase of activity of the proteins in the PI3K/Akt pathway, 6q and 10q deletions are the strongest indicators of a poor prognosis. Molecular profiling of GM may define the critical genetic alterations underlying its pathogenesis and marked resistance to therapy. Furthermore, elucidation of these critical molecular events should identify the most suitable pathways to be targeted with the novel therapy. The most promising target in glioma therapy seems to be a PI3-kinase regulated genetic pathway P27kip1/PTEN. and anti-EGFR in EGFR [+]/P53 [-] patients. As oligodendrogliomas and GM displaying oligodendroglial features, tumors with 1p and 19q deletions show better therapeutic responsiveness to chemotherapy. Recently, gene microarray analysis has further demonstrated a different expression patterns of a several hundred of genes in the GM and low-grade gliomas. Microarray analysis is a very effective method to obtain gene expression profiling in tumors.